STRATEGI GURU PENDAMPING KHUSUS DALAM MELAKSANAKAN PEMBELAJARAN PADA ANAK ADHD DI SEKOLAH DASAR 01 TELAGASARI - Widiastuti, Ridahani; Putri Pramesti, Amellya Erza; Rizqullah, Aisha Irta; Minsih, Minsih (Jurusan Pendidikan Luar Biasa, 2024)
Special Assistant Teacher Strategies in Implementing Learning for ADHD Children at Telagasari01 Elementary School. This research aims to describe the strategies of special assistant teachers in classroom learning towards inattentive behavior in ADHD children at Telagasari 01 elementary school. The type of research used is qualitative research. In this research, the data collection techniques used were observation and interviews. The subjects of this research were special assistant teachers, class teachers and observers in class 3 which contained ADHD students and directly observed the behavior or attitudes of ADHD students during the learning process at SD 01 TELAGASARI. The results of this research are that special support teachers play an important role in providing support that is appropriate to children's special needs. Effective strategies from accompanying teachers involve a direct, personal approach to children with ADHD. At SD 01 TELAGASARI, special assistant teachers work together with class teachers to provide adaptive learning for students with special needs. The strategies used include involving ADHD children in activities and providing positive incentives rather than excessive punishment to increase their motivation to learn